2020
DOI: 10.21203/rs.3.rs-31488/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What Evidence Informs the Nursing Care of People with Class III Obesity in an Acute Care Setting? A Scoping Review.

Abstract: Background: Obesity is a complex psycho-social construct which is strongly linked with health and well-being. The health and socioeconomic impacts of obesity on individuals and health care systems can be significant. The nursing care of people with Class III obesity needs careful attention to ensure the provision of appropriate care. This scoping review aims to synthesise available evidence on the nursing care of Class III obese patients in acute care settings. Methods : A scoping review informed by the Joanna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(49 reference statements)
0
3
0
Order By: Relevance
“… 148 Nursing care is always more difficult: the possibility of more precarious hygiene and secondary contamination, as well as harder venipuncture and more likelihood to cause injury; control procedures such as blood pressure measurement and cardiac auscultation are more difficult and more error-prone; and the risk of bedsores during intensive care unit stay is always higher the higher the patient’s weight. 149 …”
Section: Pathophysiology Of Obesity and Its Relationship With Covid-1mentioning
confidence: 99%
“… 148 Nursing care is always more difficult: the possibility of more precarious hygiene and secondary contamination, as well as harder venipuncture and more likelihood to cause injury; control procedures such as blood pressure measurement and cardiac auscultation are more difficult and more error-prone; and the risk of bedsores during intensive care unit stay is always higher the higher the patient’s weight. 149 …”
Section: Pathophysiology Of Obesity and Its Relationship With Covid-1mentioning
confidence: 99%
“…148 Nursing care is always more difficult: the possibility of more precarious hygiene and secondary contamination, as well as harder venipuncture and more likelihood to cause injury; control procedures such as blood pressure measurement and cardiac auscultation are more difficult and more errorprone; and the risk of bedsores during intensive care unit stay is always higher the higher the patient's weight. 149 For families, supportive measures that provide high quality information and guidance to help them make decisions on medications, the need to go to the emergency room, and how to conduct emergency care are essential. 129 For adolescents, adequate information can often aid to minimize extreme behaviors, both in the aspect of excessive fear, for some, and in the sense of invulnerability, for others.…”
Section: Final Considerations and Complications For Treatmentmentioning
confidence: 99%
“…A preliminary search of PROSPERO, MEDLINE, the Cochrane Database of Systematic Reviews, and JBI Evidence Synthesis was conducted. A current inprogress protocol 18 was identified that focuses on patient satisfaction with ICU follow-up care; however, our protocol differs from the previously registered protocol on PROSPERO 18 as it aims to explore critical illness survivors' overall experiences and perceptions of attending an ICU follow-up service, some of which may commence during inpatient stay and continue post-discharge to the community.…”
Section: Introductionmentioning
confidence: 99%